E-Portfolio: from the perspective of pre-service teachers / Jasmine Jain & Johan Eddy Luaran - Jain, Jasmine; Luaran, Johan @ Eddy (Penerbit UiTM (UiTM Press), 2015)
There has been a huge transformation in the educational assessment where educators move from traditional pen and paper tests to other alternative forms of assessment. This resulted in the use of e-portfolio as a tool for assessment for students to document their learning process. This paper studied 15 pre-service teachers' views through semi-structured interview sessions. The focus of the interviews was to investigate the pre-service teachers' perspectives on the benefits and challenges of using e-portfolio as part of their module assessment. It resulted in three categories for the benefit (Articulation of ideas; allows creativity and allows deeper reflection) and challenges (Fair use; time limitation and neglecting content) of using e-portfolio respectively. This paper also further probed on the criteria of e-portfolio hosts that attracted the pre-service teachers to use as platforms to park their e-portfolio. The three categories for the criteria for e-portfolio hosts are user-friendly, compatibility with mobile gadgets and level of familiarity.